Kesetimbangan natrium di dalam campuran biodiesel gliserol - Supriyono Supriyono; Kurnia Wijayanti (Jurnal Rekayasa Proses, 2008)
Transesterification is one of the processes for producing biodiesel. The process involves the use of liquid catalyst such as NaOH. However, the presence of Na+ ions in biodiesel accelerates the scale formation and aggravates the combustion engine performance. Therefore, the maximum concentration of Na+ is about 5 mg / kg biodiesel to minimize the effect. Recently, the focus study of transesterification using NaOH as a catalyst is achieving higher conversion. Meanwhile, the reduction process of Na+ remaining in the biodiesel has not yet been studied. The experiments were carried out in a three-neck flask equipped with a reflux condenser where jatropha oil was reacted with methanol. The amount of methanol was 3 times of the stoichiometric molar ratio, while NaOH was used as catalyst. The concentration of Na+ both in the glycerol and biodiesel phases were analyzed. Based on the excess Gibbs free energy, the maximum concentration of NaOH for transesterification of Jatropha oil was 0.0015% weight.